A high-fidelity model for FPMSM considering spatial harmonics, mutual inductance, and load change. (November 2022) - Zhu, Songling; Sun, Tianfu; Long, Linghui; Liang, Jianing; Feng, Wei
Abstract: In this paper, a high-fidelity and computationally efficient model for five-phase permanent magnet synchronous machines (FPMSMs) is proposed. The nonlinear machines parameters in the fundamental subspace and 3rd subspace are accurately modeled. The spatial harmonics related to rotor position, the mutual inductances between d–q axes and subspaces, and the flux saturations changing with current vector variations are considered. The proposed model is compared with finite element analysis (FEA) results and existing modeling techniques. It is shown that the proposed method can model the FPMSMs with higher accuracy compared with the state-of-the-art methods.